Characteristics of Rotavirus, ETEC, and Vibrio Cholerae Among Under 2-year Children Attending an Urban Diarrheal Disease Hospital in Bangladesh. (October 2021) - Sarker, Mohammad Habibur Rahman; Moriyama, Michiko; Rahman, Md Moshiur; Das, Sumon Kumar; Uzzaman, Md Nazim; Das, Jui; Uddin, Aftab; Banu, Shakila; Khan, Soroar Hossain; Shahid, Abu SMSB; Shahunja, K. M.; Chisti, Mohammod Jobayer; et al.
Background: Information on comparative clinical and host characteristics of under-2 children with watery diarrhea caused by rotavirus, Enterotoxigenic Escherichia coli (ETEC), and Vibrio cholerae as single pathogens is lacking. We sought to investigate the sociodemographic, clinical, and host characteristics of under-2 children hospitalized due to these pathogens. Methodology: We conducted a hospital-based case-control study using the icddr, b Diarrheal Diseases Surveillance System. Children of either sex, <2 years with diarrhea, who attended the hospital during 2014 to 2018, constituted the study population. Stool specimens having a single pathogen like rotavirus, ETEC, or Vibrio cholerae constituted the cases and stool specimens having no detectable common enteropathogens comprised the controls. Multinomial logistic regression analysis was done where control was the reference group. Results: A total of 14 889 patients were enrolled, 6939 of whom were under-2 children, and 5245 (76%) constituted our study population. Among them 48% (n = 2532), 3% (n = 148) and 1% (n = 49) had rotavirus, ETEC, and Vibrio cholera, respectively. A control group (diarrhea without these 3 or Shigella, Salmonella, Aeromonas ) accounted for 48% (n = 2516). In multinomial regression model, children with rotavirus (adjusted odds ratio [aOR], 1.36; 95% confidence interval [95% CI], 1.19-1.55) less often presented with dehydrating diarrhea compared to those with ETEC (aOR, 1.54; 95% CI, 1.05-2.26) and cholera (aOR, 2.25; 95% CI, 1.11-4.57). Rotavirus diarrhea was associated (aOR, 1.25; 95% CI, 1.07-1.46) with those who received antimicrobials prior to hospital admission and protectively associated with drinking tap water (aOR, 0.84; 95% CI, 0.73-0.95); however, ETEC diarrhea had protective association (aOR, 0.62; 95% CI, 0.43-0.92) with children who received antimicrobials prior to hospital admission and was associated with drinking tap water (aOR, 1.78; 95% CI, 1.19-2.66). Use of intravenous fluid was associated with cholera (aOR, 10.36; 95% CI, 4.85-22.16) and had protective association with rotavirus episodes (aOR, 0.64; 95% CI, 0.45-0.91). Conclusions: Clinical presentations and host characteristics of rotavirus, ETEC, and Vibrio cholerae diarrhea differed from each other and the information may be helpful for clinicians for better understanding and proper management of these children.